Who`s in a better mood? Comparison of behavioral indicators in horses trained with negative or positive reinforcement - Briefer, S.; Briefer, E. F.; Gindrat-von Allmen, Y.; Wyss, C.; Zollinger, A.; Bachmann, I. (Embracing science to enhance equine welfare and horse-human interactions, 2013)
Traditionally, horses are trained using negative reinforcement (NR). Recently, methods integrating positive reinforcement (PR; e.g. clicker training) have become more common. This study aimed to compare the effect of NR and PR on horse affective states, using well known behavioral and physiological indicators. Over a 5-day period, 12 mares were trained for 15 min/day using either NR (n=6) or PR (n=6) to achieve various tasks: lead in hand, stop, back up, lowering the head, walk on a tarp and stand on a platform. PR horses were trained using the clicker method and learned to follow a target. NR horses were exposed to a gradual pressure intensity which was removed as soon as the expected response was shown. Shaping procedure was applied in both PR and NR. The horses` behavior was analyzed visually from videos of the training, using a onezero sampling with 10 s intervals. Four parameters with 3 well-described descriptive levels were recorded: muscular tension (irritated; indifferent; motivated), ear position (backward; sideways; forward), attitude towards trainer (avoid contact; neutral; search contact), head position (low; middle; high). The proportion of occurrence for each parameter was calculated. Heart rate (HR) and its variability (RMSSD), respiration rate and skin temperature were recorded using a BioHarnessTM. Our results showed that during training, NR horses spent most of the time in an indifferent attitude (NR=69±2, PR=13±3, U=7, p<0.001). They also showed more irritated body tension, while PR horses expressed more motivated body tension. PR horses pointed their ears forward more often than NR horses (PR=42±2, NR=14±1, U=152, p<0.001).The latter had their ears backwards > half the time. PR horses were more likely to search contact with the trainer, whereas NR horses had a rather neutral attitude towards him. The physiological measures showed no differences between the groups. Behavioral observations suggested that horses trained with PR were in a more positive affective state than NR horses. Thus, the integration of PR in horse training may be beneficial for horse welfare. Layperson`s paragraph: While NR horses displayed a rather indifferent attitude towards the trainer, PR horses seemed to be in a more positive affective state.